Millets: Ancient Grains for Modern Nutrition - A Comprehensive Review - Navjot Kaur; Bhagyasri Ray; Chellakannan Vasantha Kalyani (Wolters Kluwer Medknow Publications, 2024)
Millets are a group of small, drought-resistant grains that have been grown for more than thousands of years. They are highly nutritious, rich in essential vitamins and minerals, and have gained attention in recent years due to their potential to address global food security and environmental challenges. This review article provides an overview of millets, their nutritional benefits, environmental advantages, and their role in promoting sustainable agriculture and processing of millets. The article also discusses the various types of millets, their cultivation, and their potential to improve human health and combat malnutrition.